Peptide-guided functionalization and macrocyclization of bioactive peptidosulfonamides by Pd(II)-catalyzed late-stage C–H activation - Jian Tang (Nature Portfolio, 2018)
Aryl sulfonamides and sultams are important pharmacophores in medicinal chemistry. Here, the authors report a practical palladium-catalyzed C–H activation assisted by amino-acid residues in the substrate leading to arylsulfonamides and bioactive peptidosulfonamide macrocycles.